STRATEGI EDUKASI GIZI DAN EFEKTIVITAS MEDIA POSTER SEBAGAI IMPLEMENTASI KELUARGA SADAR GIZI (KADARZI) - Rizki Natia Wiji; Imelda Fitri (LPPM Universitas Abdurrab, 2020)
Lowness of the nutrition Awareness family (Kadarzi) percentage only 29,6%. Low birth weight about 104 cases on January until July of 2018 at the Arifin Achmad Regional Hospital. Facing the lack behavior in the in the healthy lifestyle as long as the pregnancy. This study aimed to develop the poster media as the strategic education for the medical, maternal infant and Balita’s, then knowing effectivity of the poster media as the reach effort to Kadarzi at the Arifin Achmad Regional Hospital of Riau Province. Type of the study was analytic descriptive with desain used in this study quasi experiment pretest posttest one group with qualitative and quantitative methods.The samples taken for test implementation nutrition education was 27 medical group and the sampel taken for nutritional education was 48 puerperal maternal and mothers which has the baby and infant. Educational messages developed were advice exclusive breastfeeding,weighing for children under five regularly, eating the iodine salt, eating the variant food, consuming the supplement as the patter. Data was analyzed by using t Dependen test. The effectivity test outcome of the poster media Kadarzi showing more than 80% of the respondent’s knowledge increased better than before and (p=0,000). There was effectivity of the poster media as the education strategic for the medical, puerperal maternal and maternal which had the baby and infant as the reach Kadarzi at the Arifin Achmad Hospital of Riau. Conclusion: the nutrition education posters which were made fairly, simple, easy to understand and universal effective were able to improve the nutritional knowledge of puerperial, and infant mother